Effect of a 24-Week Concurrent Exercise Intervention on Neck Adiposity and Its Distribution in Young Adults: The ACTIBATE Randomized Controlled Trial - Arias-Tellez Maria Jose; Acosta Francisco M.; Merchan-Ramirez Elisa; Martinez-Tellez Borja; Delgado Guillermo-Sanchez; Llamas-Elvira Jose M.; Ruiz Jonatan R. (HUMAN KINETICS PUBL INC, 2025)
Neck adipose tissue (NAT) accumulation and neck circumference are independent predictors of cardiometabolic risk (CMR) and low-grade chronic inflammation in young adults. The present study examines whether a 24-week concurrent exercise intervention can reduce NAT volume and neck circumference in young adults, and whether any changes in these variables are related to changes in body composition, CMR, and the inflammatory profile. Seventy-four participants (51 women, age 22 & PLUSMN; 2 years) were included in the main analyses, after being randomly assigned to either a (a) control (n = 34), (b) moderate-intensity exercise (n = 19), or (c) vigorous-intensity exercise (n = 21) group. Participants in the exercise groups trained 3-4 days/ week (endurance + resistance exercise training). NAT volume and NAT distribution across different depots were estimated using computed tomography before and after the intervention. Anthropometric variables, body composition (determined by dual-energy X-ray absorptiometry), and CMR/inflammatory markers were also recorded. The exercise intervention did not reduce the total NAT volume, nor was NAT distribution affected (p > .05). However, it did reduce neck circumference in the vigorous-intensity exercise group compared with the moderate-intensity exercise and control groups (by 0.8 and 1 cm, respectively, p <_ .05). Changes in total NAT and neck circumference were positively, albeit weakly, related (adj. R2: .05-.21, all p <_ .05) to changes in body weight and adiposity, leptin (only total NAT), and CMR (only neck circumference). Altogether 24 weeks of concurrent exercise does not appear to reduce NAT accumulation in young adults, but may slightly reduce neck circumference in those who in exercise.